Advancements in Nanomedicine for the Diagnosis and Treatment of Kidney Stones - Wang Y; Yang J; Amier Y; Yuan D; Xun Y; Yu X (International Journal of Nanomedicine)
Yongqi Wang, Junyi Yang, Yirixiatijiang Amier, Dongfeng Yuan, Yang Xun, Xiao Yu Department of Urology, Institute of Urology, Tongji Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, People’s Republic of ChinaCorrespondence: Yang Xun; Xiao Yu, Department of Urology, Tongji Hospital, Tongji Medical College, Huazhong University of Science and Technology, Liberalization Ave, No. 1095, Wuhan, 430030, People’s Republic of China, Email tjxyang1993@163.com; yujiuhu@163.comAbstract: Kidney stones constitute a common condition impacting the urinary system. In clinical diagnosis and management, traditional surgical interventions and pharmacological treatments are primarily utilized; however, these methods possess inherent limitations. Presently, the field of nanomedicine is undergoing significant advancements. The application of nanomaterials in biosensors enables the accurate assessment of urinary ion composition. Furthermore, contrast agents developed from these materials can improve the signal-to-noise ratio and enhance image clarity. By mitigating oxidative stress-induced cellular damage, nanomaterials can inhibit the formation of kidney stones and enhance the efficacy of drug delivery as effective carriers. Additionally, by modifying the physical and chemical properties of bacteria, nanomaterials can effectively eliminate bacterial presence, thereby preventing severe complications. This review explores the advancements in nanomaterials technology related to the early detection of risk factors, clinical diagnosis, and treatment of kidney stones and their associated complications.Keywords: nanomaterials, kidney stones, oxidative stress, biomaterial